Looking back and moving forward: can we accelerate progress on adolescent pregnancy in the Americas? - Sonja Caffe; Marina Plesons; Alma Virginia Camacho; Luisa Brumana; Shelly N. Abdool; Silvia Huaynoca; Katherine Mayall; Lindsay Menard-Freeman; Luis Andres de Francisco Serpa; Rodolfo Gomez Ponce de Leon; Venkatraman Chandra-Mouli (BMC, 2017)
Abstract Adolescent fertility rates in Latin America and the Caribbean (LAC) remain unacceptably high, especially compared to the region's declining total fertility rates. The Region has experienced the slowest progress of all regions in the world, and shows major differences between countries and between subgroups in countries. In 2013, LAC was also noted as the only region with a rising trend in pregnancies in adolescents younger than 15 years. In response to the lack of progress in the LAC region, PAHO/WHO, UNFPA and UNICEF held a technical consultation with global, regional and country-level stakeholders to take stock of the situation and agree on strategic approaches and priority actions to accelerate progress. The meeting concluded that there is no single portrait of an adolescent mother in LAC and that context and determinants of adolescent pregnancy vary across and within countries. However, lack of knowledge about their sexual and reproductive health and rights, poor access to and inadequate use of contraceptives resulting from restrictive laws and policies, weak programs, social and cultural norms, limited education and income, sexual violence and abuse, and unequal gender relations were identified as key factors contributing to adolescent pregnancy in LAC. The meeting participants highlighted the following seven priority actions to accelerate progress: 1. Make adolescent pregnancy, its drivers and impact, and the most affected groups more visible with disaggregated data, qualitative reports, and stories. 2. Design interventions targeting the most vulnerable groups, ensuring the approaches are adapted to their realities and address their specific challenges. 3. Engage and empower youth to contribute to the design, implementation and monitoring of strategic interventions. 4. Abandon ineffective interventions and invest resources in applying proven ones. 5. Strengthen inter-sectoral collaboration to effectively address the drivers of adolescent pregnancy in LAC. 6. Move from boutique projects to large-scale and sustainable programs. 7. Create an enabling environment for gender equality and adolescent sexual and reproductive health and rights.